Evaluating Sustainable Ecotourism Practices from the Integrated Perspective of Stakeholders; in Lekki Conservation Center - Umar, Abdullahi Abba (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2023)
The development and promotion of economic growth of the specific tourism activities within that area, community engagement in protected areas, and community-based tourism management are crucial to that region's environmental sustainability. To determine how the local community can work with the management of the Lekki Conservation Center to successfully promote the center for the benefit of tourists and how their intention will result in revisiting intentions to the conservation center, the study sought to examine the parameters and measures of local community participation. For accurate observation of linked research, a variety of literature on the development of ecotourism, community-based tourism, stakeholder theories, and complexity in sustainability was evaluated. Furthermore, because the research was focused on respondents' perceptions, it tended to use a qualitative strategy for gathering data. To get further data for the study, the researchers used theoretical collaboration to provide through semi-structured interviews, the researcher's physical observation, and group discussions with the pertinent Respondents. The local community, the management of the conservation center, and the tourists were the subjects of the semi-structured interview, which was done in three stages. Tables representing the socioeconomic traits of the respondents and a picture of the conservation facility were used to examine the data. The outcome demonstrates that the majority of the local communities reasonably implemented community engagement in preserving the conservation center for the center and their safety. In terms of community involvement in decision-making, the findings indicate that residents were excluded from management decision-making. This occurred as a result of local communities' involvement in the illegal destruction of the conservation center's forest, which for a long time served as a barrier between them. The study advises and suggests that the management should assist the small and medium-sized enterprises in the area with funding to increase investments for visitor happiness, which would afterward directly benefit the conservation center. However, the study recommends management assist the local people with the biggest concerns of monkey infiltration into their homes to prevent a disease outbreak similar to the Ebola virus outbreak in east Africa.

ÖZ : O bölgedeki belirli turizm faaliyetlerinin ekonomik büyümesinin geliştirilmesi ve teşvik edilmesi, ayrıca korunan alanlarda toplum katılımı ve toplum temelli turizm yönetimi, o bölgenin çevresel sürdürülebilirliği için çok önemlidir. Turistlerin yararına merkezi başarılı bir şekilde tanıtmak için yerel halkın Lekki Koruma Merkezi yönetimiyle nasıl çalışabileceğini ve niyetlerinin koruma merkezine tekrar ziyaret etme niyetleriyle nasıl sonuçlanacağını belirlemek için çalışma, parametreleri ve önlemleri incelemeye çalıştı. yerel topluluk katılımı. Bağlantılı araştırmanın doğru bir şekilde gözlemlenmesi için ekoturizmin gelişimi, topluluk temelli turizm, paydaş teorileri ve sürdürülebilirliğin karmaşıklığı üzerine çeşitli literatür değerlendirildi. Ayrıca, araştırma katılımcıların algılarına odaklandığından, veri toplamak için nitel bir strateji kullanma eğilimindeydi. Araştırma için daha fazla veri elde etmek amacıyla araştırmacılar, yarı yapılandırılmış görüşmeler, araştırmacının fiziksel gözlemi ve ilgili Katılımcılarla grup tartışmaları yoluyla teorik işbirliğini kullandılar. Üç aşamada gerçekleştirilen yarı yapılandırılmış görüşmenin konusu yerel halk, koruma merkezi yönetimi ve turistlerdir. Verilerin incelenmesinde, katılımcıların sosyoekonomik özelliklerini temsil eden tablolar ve koruma tesisinin resmi kullanılmıştır. Sonuç, yerel toplulukların çoğunluğunun, koruma merkezini merkez ve onların güvenliği için korumak için topluluk katılımını makul bir şekilde uyguladığını göstermektedir. Karar alma sürecine toplumun katılımı açısından, bulgular bölge sakinlerinin yönetimin karar alma sürecinden dışlandığını göstermektedir. Bu, yerel toplulukların uzun süre aralarında bir bariyer görevi gören koruma merkezinin ormanının yasa dışı olarak yok edilmesine karışmasının bir sonucu olarak meydana geldi. Çalışma, yönetimin bölgedeki küçük ve orta ölçekli işletmelere daha sonra doğrudan koruma merkezine fayda sağlayacak olan ziyaretçi mutluluğuna yönelik yatırımları artırmak için fon sağlama konusunda yardımcı olması gerektiğini tavsiye ediyor ve öneriyor. Bununla birlikte, çalışma, yönetimin, doğu Afrika'daki Ebola virüsü salgınına benzer bir hastalık salgınını önlemek için evlerine maymun sızmasıyla ilgili en büyük endişeleri olan yerel halka yardım etmesini öneriyor.
Master of Science in Tourism Management. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Tourism, 2023. Supervisor: Asst. Prof. Dr. Hamed Rezapouraghdam
Keywords: Thesis Tez; Tourism Faculty; Tourism Sector--Ecotourism Initiatives--Lekki Conservation Center--Lagos (Nigeria); Tourism--Sustainable tourism--Lekki Conservation Center--Lagos (Nigeria); Ecotourism--Nature conservation--Nigeria; Sustainable Ecotourism; Local Community Participation; Stakeholder’s Perspective